Power system stabiliser PSS4B-W parameters optimisation and RTDS test verification - Guo, Siyuan; Zhang, Shoushou; Zhu, Weijun; Li, Li; Li, Hui (Journal of engineering (Stevenage, England), 2019)
This study introduces the mathematical model of a new type of power system stabiliser PSS4B-W. The concept of crossbreed in genetic algorithm is introduced to particle swarm optimisation algorithm and applied to PSS4B-W parameter optimisation. With a PCS-9410 excitation regulator, the semi-physical simulation system is constituted on a real time digital simulator (RTDS) platform. By measuring the excitation system phase frequency characteristic without compensation, the PSS4B-W parameter optimisation is converted to a set of parameters optimisation process with inequality constraint. In the RTDS platform, the time-domain dynamic response of without PSS, adding PSS2B and PSS4B-W, is compared and analysed. Simulation results show that the optimised PSS4B-W can provide effective damping in different frequency bands, and have good inverse-regulation suppression effect.